Kajian Stabilitas Lereng dengan Perkuatan Geotekstil dan Dinding Penahan Tanah Kantilever di Ruas Jalan Padang-Lb. Selasih Sumatera Barat - Syahril Alzahri; Adiguna; Bimo Brata Adhitya; Yulindasari Sutejo; Reffanda Kurniawan Rustam (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2020)
A typical relatively steep slope makes the Lb. Selasih – Bts. Kota Padang KM.29+650 experienced a landslide in 2017. So, it is necessary to strengthen the slope to overcome the landslide. Alternative slope reinforcement used is reinforcement using cantilever retaining walls or geotextiles. Slope stability analysis before and after were analyzed using the Slope/W program. The output produced by Slope/W program is the value of the safety factor. The safety factor value for the state of the original slope is 1.100. It shows that the slope in the original condition is unstable and vulnerable to landslide hazards. The retaining wall has a height of 11 m and a base plate width of 8 m. The results of the analysis showed that the cantilever retaining wall securely with stands shear, rolling, and bearing capacity of the subgrade with a safety factor value of 1.620; 1.550; 2.160, while geotextile reinforcement has a height of 16 m and an ultimate tensile strength of 200 kN / m. The results of the analysis showed that the reinforcement of the geotextile safely sliding, stability, and bearing capacity of the subgrade with a safety factor value of 1.600; 2.330; 2.860. Both of these reinforcements are safe to stabilize the slope by increasing the value of the slope safety factor by 2.235 for strengthening the cantilevered retaining wall and 2.279 for strengthening the geotextile.